Characterization of fur regulatory region of local Pasteurella multocida 6:B isolate / Nurul Azyla Azmi - Azmi, Nurul Azyla (2013)
Haemorrhagic Septicaemia (HS) is a major disease of cattle and buffaloes characterized by an acute, highly fatal septicaemia with high morbidity and mortality. In Asia, HS is caused by Pasteurella multocida serotype B:2 or 6:B. The production of iron regulated outer membrane proteins (IROMPs) is regulated by Fur protein through repression of the expression of the respective genes when complexed with iron. In this study, outer membrane proteins (OMPs) and iron-regulated outer membrane proteins (IROMPs) were prepared by extraction with 1.5 % sarcosyl from a Pasteurella multocida 6:B local isolate cultured on BHI medium and on a medium supplemented with different concentration of 2,2’-dipyridyl. Outer membrane proteins from the isolate were characterized by using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) technique. The approximate size of each OMPs detected were determined from log of molecular weight and Rf value. A total of 12 polypeptides ranging from 19.2 to 117.4 kDa were observed, including 33 and 37kDa major OMPs of Pasteurella multocida and two other (117.4 and 91kDa) prominent protein bands. In another study, several primers were designed for amplification around the fu r gene. Sequence analysis from the amplified DNA revealed an additional sequence of 718bp upstream from fu r gene which was unique to the local isolate of Pasteurella multocida 6:B as compared to Pasteurella multocida (PM70). BLAST analysis showed that the sequence possess significant identity towards partial sequence of Pasteurella multocida P934 region 2 capsule biosynthesis gene cluster. The potential of this additional sequence as a specific marker for rapid identification of HS diagnosis in Malaysian outbreak should be considered. A study on the function of this gene should also be carried out to give a better understanding of the specific serotypes that causes HS outbreak in Malaysia.